Plant diversity in the understory of Eucalyptus plantations on Hainan Island and its response to environmental factors - Chen, Haihui; Du, Shan; Huang, Hai; Tian, Leyu; Zhou, Hua; Wu, Jinqun; Yu, Xuebiao (Frontiers in Ecology and Evolution, 2024)
Research on understory plant diversity and its response to environmental factors helps in the sustainable development of plantation forests. In view of this, we investigated the characteristics of understory plant diversity and its response to environmental factors in Eucalyptus plantation forests on Hainan Island, China. A total of 124 plant species belonging to 62 families and 112 genera were recorded in the sampled plots of the Dongfang, Ding'an, Tunchang, and Lingao regional sites on Hainan Island, among which species of Fabaceae and Poaceae comprised the largest number of plants.The number of species and plant diversity indices of the shrub layer and herb layer in Eucalyptus plantation forests varied at different sites. Tunchang, located in the center of Hainan Island, had the richest understory vegetation and the highest α-diversity whether gauged by species or phylogenetically. The similarity of the understory plant community species was greatest between Ding'an and Tunchang, whereas the difference in composition was largest between Dongfang and the other three sites. Phylogenetically, the understory plant community at Ding'an had the most distant affinities among species, whereas that at Tunchang had the closest affinities among species. The results of the Mantel test and redundancy analysis revealed differing correlations between plant diversity in the shrub layer versus herb layer and various environmental factors. In particular, elevation and annual average temperature are the two main factors influencing plant diversity in the shrub layer, and soil available nitrogen and annual average sunshine duration are the two main factors influencing plant diversity in the herb layer. Variance decomposition showed that the combined effect of soil, climate, and topography factors is the main driver shaping plant diversity in the shrub layer of the understory in Eucalyptus plantation forests, while the combined effect of climate and soil factors is the main one determining plant diversity in their herb layer.